The meg [videorecording (DVD)] - Georgaris, Dean; Hoeber, Jon; Hoeber, Erich; Statham, Jason, 1967-; Li, Bingbing, 1976-; Wilson, Rainn, 1966-; Rose, Ruby, 1986-; Chao, Winston; Kennedy, Page, 1976-; McNamee, Jessica, 1986-; Ólafur Darri Ólafsson; Taylor, Robert, 1963-; et al. (Warner Bros. Home Entertainment, 2018)
A deep-sea submersible filled with an international research crew lies disabled at the bottom of the Pacific after having been attacked by a massive shark previously thought to be extinct. With time running out, expert deep sea rescue diver Jonas Taylor is recruited by a visionary Chinese oceanographer to save the crew and the ocean itself from this unstoppable threat that is a pre-historic 75-foot-long shark known as the Megalodon.